PERSEPSI SISWA DALAM PELAKSANAAN PEMBELAJARAN IPS DI KELAS XI SMA NEGERI 2 DHARMASRAYA - Kusnando, Digo - (Pendidikan Geografi, 2014)
Problems in the study of learning materials IPS that too many students so hard to digest the material being studied, hours of social studies are limited due to lack of fit with existing materials and methods used monotonous teacher. The purpose of this research is to obtain information and make a description of students perceptions of the learning process from the aspects of learning material, hours of study, methods of teaching and learning aids. This study used a descriptive percentages. The population in this study was a class XI student of SMAN 2 Koto Baru Dharmasraya numbering as many as 180 people, while the samples in this study were 90 students drawn at random sampling of the population. Means of data collection in this study is the documentation and questionnaires or questionnaire.